MHD natural convection in a partially open trapezoidal cavity filled with a nanofluid - Miroshnichenko, Igor V.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2016)
A numerical study of natural convection in a partially open trapezoidal cavity filled with a CuO nanofluid under the effect of uniform magnetic field of various orientations has been carried out. Inclined wall of the cavity is heated, horizontal walls are adiabatic while cold nanofluid enters into the cavity from an open boundary. To analyze the effects of magnetic field intensity and its inclination angle with nanoparticles volume fraction, the finite difference method has been utilized to solve the governing equations formulated in dimensionless stream function, voracity and temperature. Analysis has been conducted in a wide range of governing parameters such as Rayleigh number (Ra=10(3)-10(5)), Prandtl number (Pr=7.0), Hartmann number (Ha=0, 10, 50, 100), inclination angle of magnetic field (alpha=0-pi) and nanoparticles volume fraction (0 <=phi <= 0.04). It has been found that an increase in Hartmann number leads to the heat transfer reduction, while an increase in the nanoparticles volume fraction reflects the heat transfer enhancement.
Keywords: Natural convection; Inclined uniform magnetic field; Nanofluid; Partially open trapezoidal cavity; Numerical results